Exploring the Conceptual Relationship between Motivation and Employee Optimal Performance in the Manufacturing Industry in South Africa - Jam-Jam, Sinekaya; Mbukanma, Ifeanyi (The Journal of Accounting and Management, 2024)
Abstract: The objective of this study was to explore the conceptual relationship between motivation and employee optimal performance in a manufacturing industry in South Africa. To achieve this objective, an exploratory literature review approach to research was employed, where information and deliberations on employee motivation, optimal performance, and the manufacturing industry were obtained from journals and publications of previous scholars, both local and international. This study’s findings revealed a significant positive impact of financial motivation, which includes salary increases, cash allowance, bonuses, and retirement benefits, with employees’ optimal performance in South Africa. Similarly, non-financial motivations such as position promotion, the award for recognition, training, and development, and involvement in decision-making were also ascertained to significantly positively impact employees’ optimal performance in manufacturing industries in South Africa. Previous literature was also found to agree that many employees agreed that award of recognition can stimulate employees to perform optimally in their job deliverables. It was recommended that organisations such as manufacturing industries should employ both financial and non-financial motivations as identified in this study to enhance employee optimal performance.